Resilience in Public Sector Managers. (June 2022) - Plimmer, Geoff; Berman, Evan M.; Malinen, Sanna; Franken, Esme; Naswall, Katharina; Kuntz, Joana; Löfgren, Karl
This study discusses the concept of employee resilience (ER), defined as the capability to use resources to continually adapt and flourish at work, even when faced with challenging circumstances. The concept is grounded in positive psychology and conservation of resources (COR) theory and complements other concepts such as coping which describe employees and managers adapting to challenge and change. This study validates a scale of ER and examines attributes and job factors associated with heightened ER in public sector line managers. Study results show that heightened ER is associated with public service motivation (PSM), employees' pro-social skills and constructive leadership by supervisors. ER is also associated with a climate for innovation. Theoretical and practical implications for strengthening employees' resilience in public organizations are discussed.